Information System for Determining Student Achievement Using the K-Means Method - Wenny Yulia Cahya (International Journal of Mechanical Computational and Manufacturing Research, 2023)
Value is an important thing in the world of education and requires a special processing and policy, both in its use, maintenance and recording. Because of the importance of using this value, it is necessary to carry out systematic and effective processing of the values ​​obtained by students. Processing grades consisting of formative grades, assignment grades, and semester grades for each student. To calculate the student's grades, the K-Means method was used to determine students who excel at SMA Swa Bina Karya. The information system for determining outstanding students at Swa Bina Karya High School is still manual. Where the process of recording and calculating student grades is still manual where the recording of each student's grades is recorded in the gradebook owned by each homeroom teacher so that the process of making class ranking reports requires a lot of time and the resulting information is less effective and efficient. To be able to overcome this frequent problem, the authors designed a system for determining student achievement using the K-Means method using Microsoft Visual Basic.Net 2008 and the database used was Sql Server 2008. With the design of this system, the homeroom teacher and school principal can receive more accurate and timely class ranking reports. Besides that, this system also helps admin work much more effectively and efficiently